A review of the law surrounding female genital mutilation protection orders. (2nd July 2020) - Home, Joseph; Rowland, Andrew; Gerry, Felicity; Proudman, Charlotte; Walton, Kimberley
Abstract : Performing female genital mutilation (FGM) is prohibited within the UK by the FGM Act of 2003. A mandatory reporting duty for FGM requires regulated health and social care professionals and teachers in England and Wales to report known cases of FGM in under 18-year-olds to the police. An application to the court for an FGM protection order (FGMPO) can be made to keep individual women and girls safe from FGM. This paper reveals the significant disconnect between the number of FGMPO applications and known recorded cases of FGM. The introduction of FGMPOs requires critical exploration as there is insufficient evidence to show that FGMPOs are effective in protecting women and girls from FGM. It is therefore unclear what impact, if any, FGMPOs are having upon the protection of women and girls at risk of FGM. The barriers to the implementation of FGMPOs and possible solutions are discussed.